1975
DOI: 10.1161/01.cir.52.5.766
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of antegrade and retrograde conduction patterns in man.

Abstract: SUMMARYPatterns of antegrade and retrograde conduction and refractory periods were studied using His bundle electrogram recordings, incremental atrial and ventricular pacing and the extrastimulus technique. In 36/50 patients antegrade conduction was "better" than retrograde conduction (group I), as evidenced by a) onset of retrograde atrioventricular (A-V) 766 Materials and MethodsRight heart catheterization was performed in the nonsedated postabsorptive state using local anesthesia. Fifty patients were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…16 Electrophysiological study confirmed that atrial and ventricular ERPs in these patients were significantly shorter than the lower border of the normal range. 17,18 The duration of the refractory periods of the myocardium is widely recognized to be an important parameter for the vulnerability of the heart to fibrillation at both atrial and ventricular levels.…”
Section: Discussionmentioning
confidence: 99%
“…16 Electrophysiological study confirmed that atrial and ventricular ERPs in these patients were significantly shorter than the lower border of the normal range. 17,18 The duration of the refractory periods of the myocardium is widely recognized to be an important parameter for the vulnerability of the heart to fibrillation at both atrial and ventricular levels.…”
Section: Discussionmentioning
confidence: 99%
“…All pertinent conduction and refractory period intervals were measured as a part of the routine electrophysiologic study and have been previously published. 13 From the moment a sustained monomorphic VT was induced, particular attention was paid to the following. 1) Did the VT have a typical left or right bundle branch block pattern?…”
mentioning
confidence: 99%
“…AERP is achieved earlier than AVNERP, especially at a slow own rhythm or excess sympathetic tension. Noticeably, the hereby-documented reference values for the refractory periods of canine atria, atrioventricular node and ventricles differ markedly from the respective values for humans (Akhtar et al 1975;Josephson, 2002). The refractory periods of dogs turned out to be markedly shorter than those of humans.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, 13 (59%) dogs showed simultaneous block of the atrioventricular nodal and atrial conduction during the AVNERP and AERP determination. The sinoatrial node (45%), followed by the atrium (40%), are the primary sites in which the conduction block is observed during the refractory period determination in most humans (Akhtar et al 1975). AERP is achieved earlier than AVNERP, especially at a slow own rhythm or excess sympathetic tension.…”
Section: Discussionmentioning
confidence: 99%